PENGARUH BELANJA MODAL, PENDAPATAN ASLI DAERAH, DAN DANA ALOKASI UMUM TERHADAP KINERJA KEUANGAN DAERAH (Studi pada Kabupaten Aceh Tamiang) - Ayu Rohanda; Iqlima Azhar (Jurnal Mahasiswa Akuntansi Samudra, 2023)
The research was conducted with the aim of determining the influence of capital expenditure, local original income and general allocation funds on the regional financial performance of Aceh Tamiang Regency. The data used is secondary data sourced from the budget realization report (LRA) of the Aceh Tamiang Regency government. The data analysis method uses a quantitative method with multiple linear regression equation analysis. The partial t test results of local original income are significant to financial performance, while capital expenditure and general allocation funds are partially insignificant to regional financial performance. The results of the F test or simultaneously capital expenditure, local original income and general allocation funds are significant to the financial performance of the Aceh Tamiang Regency Government.